1994
DOI: 10.1046/j.1365-313x.1994.6020187.x
|View full text |Cite
|
Sign up to set email alerts
|

Water channels in the plant plasma membrane cloned by immunoselection from a mammalian expression system

Abstract: SummaryExpression in mammalian COS cells and an efficient microtiter-based strategy for immunoselectlon was used in a novel approach to identify genes encoding plant membrane proteins. COS cells were transfected with an Arabidopsis thaliana root cDNA library constructed in a bacterial mammalian shuffle vector and screened with an antiserum raised against purified deglycosylated integral plasma membrane proteins from A. thallana roots. Antibodies directed against a prominent 27 kDa antigen led to the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
258
1
4

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(280 citation statements)
references
References 37 publications
16
258
1
4
Order By: Relevance
“…OsPIP1;2, OsPIP1;3, OsPIP2;1, OsPIP2;3, OsPIP2;4, OsPIP2;5 and OsPIP2;6, were transcribed at higher rates in roots than leaves and only one PIP gene, OsPIP2;7, followed the pattern of mRNA accumulation of higher levels in leaves than roots. Inconsistency between aquaporin expression at the mRNA level and protein accumulation was also noted in a previous study [8,30]. These authors postulated that post-transcriptional mechanisms resulted in this, e.g.…”
Section: Pip Expression In Upland Rice and Lowland Rice Under Normalsupporting
confidence: 63%
“…OsPIP1;2, OsPIP1;3, OsPIP2;1, OsPIP2;3, OsPIP2;4, OsPIP2;5 and OsPIP2;6, were transcribed at higher rates in roots than leaves and only one PIP gene, OsPIP2;7, followed the pattern of mRNA accumulation of higher levels in leaves than roots. Inconsistency between aquaporin expression at the mRNA level and protein accumulation was also noted in a previous study [8,30]. These authors postulated that post-transcriptional mechanisms resulted in this, e.g.…”
Section: Pip Expression In Upland Rice and Lowland Rice Under Normalsupporting
confidence: 63%
“…Silencing water channel expression seems to reduce the ability of seeds to absorb water as a result of the water channel deficiency. However, PIP1 isoforms have often been found to have very low, or no, water permeability when expressed solely in Xenopus oocytes [22,[38][39][40]. Previously, Chaumont and his co-workers [41] have demonstrated that interactions between maize ZmPIP1;1 and ZmPIP1;2 or between ZmPIP1;2 and ZmPIP2 positively modulated their water channel activity.…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic water permeability measurements have been used in Xenopus oocytes for the identification of functional aquaporins (Preston et al, 1992 ;Maurel et al, 1993 ;Daniels et al, 1994 ;Karmmerloher et al, 1994). For such large cells, the permeability time is so long that the mixing time (when the osmotic shock occurs) can usually be neglected.…”
Section: mentioning
confidence: 99%